Narasi Lingkungan dan Pembangunan Berkelanjutan dalam Novel Karya Ahmad Tohari: Perspektif Education for Sustainable Development (ESD) - Novia Shafa Dwijayanti; Aldi Firnanda (IAIN Madura, 2026)
This research is motivated by the suboptimal use of literary works as a learning medium based on Education for Sustainable Development (ESD) in fostering environmental awareness. This study aims to identify sustainability values related to the relationship between humans and the environment and their relationship to the principles of sustainable development in Ahmad Tohari's novel. The method used is descriptive qualitative with library research. Data collection was carried out through reading and note-taking techniques. The results show that Ahmad Tohari's novel contains ESD values that represent the relationship between humans, the environment, and social systems. Teak forest management reflects the economic dimension while also demonstrating social inequality in the control of natural resources. Infrastructure development, such as bridges and irrigation channels, demonstrates complex ecological and social impacts in the development process. In addition, local wisdom in managing natural resources illustrates sustainable practices based on traditional knowledge. The environmental narrative in the novel emphasizes the importance of balance between exploitation and conservation of nature. Thus, literary works have the potential as educational media in instilling sustainability values according to ESD principles.